Trend and Online Gambling Risk: An Emerging Criminality Problem Against Youth - Henky Fernando (CV. Doki Course and Training, 2024)
The involvement of youth in online gambling cases not only shows a trend of social deviation but also has the potential to form increasingly massive criminal behaviour. However, this phenomenon has not been comprehensively discussed in previous studies. In addition to responding to the shortcomings of previous studies, this study also focuses on explaining the characteristics, factors, and implications of the trend of online gambling against youth on the potential for the formation of increasingly massive criminal behaviour. This study is descriptive qualitative by using a netnography approach. This study shows three important findings regarding the trend and risk of online gambling on the problem of criminality against youth. First, the characteristics of online gambling that are popular against youth, apart from appearing with various types of games, the involvement of youth is also not a few players and even bookmakers of online gambling. Second, the reasons underlying youth to be actively involved in online gambling cases are more influenced by structural factors than cultural factors. Third, the behaviour formed by youth who are actively involved in online gambling cases, apart from going beyond deviant behaviour, has also increased the problem of increasingly massive criminality. This study also recommends the importance of future studies that explain the reception of law enforcement and the community in interpreting the trend of deviant behaviour against youth by conducting in-depth and more intensive interviews.